Successes and failures of the "Public Entertainment Company of Almeria" : Roaring twenties? - Rodríguez López, Mauricio (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2021)
This article investigates the cultural management of the only entertainment company in Almeria between 1914 and 1921. Its main objective is to present the role that the public entertainment company formed on July, 8th 1914, played for the cultural history of the city. Although it was a decade marked by World War I, considerable efforts were made to offer quality theater every time, through the most relevant companies of the moment. After analyzing the economic successes and failures, the investigation ends with the study of the ten-year lease of the new Cervantes Theater.